Penggunaan Second Account Instagram Sebagai Media untuk Self-Disclosure - Tobing, Elalita Rumondang; Rahayu, Puspita Puji; Amaliyah, Shofwatun (CV. Lentera Literasi Indonesia, 2025)
In the digital era, social media has become the most important tool for people. One of them is Instagram, which provides a space to share information to become a place for self-disclosure. This encourages many users to have a second account on Instagram, to display things that cannot be uploaded on the main account. This research aims to find out how the use of a second Instagram account becomes a form of self-disclosure for students at Karangturi National University Semarang. This research uses a qualitative method with a total of 4 informants. Data collection techniques were carried out through interviews and observation of posts on the accounts of both students. The results showed that students of Karangturi National University use a second account to reveal themselves only to selected people, such as family or close friends. They are more open when uploading various photos and videos of their daily lives, pour out their hearts openly, and feel safe if they have to reveal another side of themselves on the second account.